Challenging perspectives on mathematics classroom communication - Chronaki, Anna; Christiansen, Iben Maj (Emerald Publishing Limited : IAP-Information Age Publishing, 2004)
The editors and contributors of these ten articles focus on the idea that communication includes both what is happening and being said among participants in a classroom and also the politics, values and ideologies that serve as the foundation of the practice. They describe how communication thereby involves register, representation and contexts through media-human interfaces in the classroom and in interpreting mathematics as a text, how communication in mathematics teaching becomes social interaction in cooperative settings and classroom activities, and how communication translates into practice, community, identity and policy.
Keywords: Mathematics -- Study and teaching -- United States.; Mathematical notation -- United States.; Communication in education -- United States.; Education -- Teaching -- Subjects -- Mathematics.; Educational: Mathematics and numeracy.; Teaching of reading, writing and numeracy.; elektronické knihy; electronic books